Bacterial protein secretion systems: Game of types. Issue 5 (10th May 2022) - Filloux, Alain
Abstract : Protein trafficking across the bacterial envelope is a process that contributes to the organisation and integrity of the cell. It is the foundation for establishing contact and exchange between the environment and the cytosol. It helps cells to communicate with one another, whether they establish symbiotic or competitive behaviours. It is instrumental for pathogenesis and for bacteria to subvert the host immune response. Understanding the formation of envelope conduits and the manifold strategies employed for moving macromolecules across these channels is a fascinating playground. The diversity of the nanomachines involved in this process logically resulted in an attempt to classify them, which is where the protein secretion system types emerged. As our knowledge grew, so did the number of types, and their rightful nomenclature started to be questioned. While this may seem a semantic or philosophical issue, it also reflects scientific rigour when it comes to assimilating findings into textbooks and science history. Here I give an overview on bacterial protein secretion systems, their history, their nomenclature and why it can be misleading for newcomers in the field. Note that I do not try to suggest a new nomenclature. Instead, I explore the reasons why naming could have escaped our control and I try to reiterate basic concepts that underlie protein trafficking cross membranes.